Growth of CuInSe2 nanoparticles by chemical vapor deposition for solar cell applications - Zhou, Zhan. (2011)
This project was designed to investigate the possibility of growing Copper Indium Diselenide (CuInSe2) nanoparticles by Chemical Vapor Deposition (CVD) for solar cell applications. The purpose was to study the reaction and deposition mechanism and to optimize the parameters of this technique. CuInSe2 nanoparticles were synthesized on the glass substrate by CVD technique using precursors Copper Iodide (CuI), Indium powder and Selenium powder. Effect of the parameters like precursor dose, precursor ratio, carrier gas flow rate, temperature and deposition time were investigated. The reaction and deposition mechanism were studied. The technique parameters were adjusted and optimized to achieve the CIS nanoparticles. Upon successful synthesizing the samples, they were characterized using various techniques. SEM, EDX, and XRD together with the measured optical parameters obtained from UV-Vis Absorption testing were analyzed and compared. The results showed that best result of the inter-connected CIS nanoparticles with average size of around 60nm were achieved by using 0.001g In, 0.002g Se and 0.001g CuI at 800°C under 400 sccm flow rate. The distance between mix precursor of In + Se and precurso CuI is 15cm, the distance between precursor CuI and the glass substrate is 2.5cm. The synthesized nanoparticles showed a blue-shift in their uv absorption curve.